Harvest phenotypes for G20 GIFT Growth line - Mahmuddin, Mahirah; Hamilton, Matthew (2025)
This Excel file contains the harvest information of the Genetically Improved Farmed Tilapia (GIFT), generation 20. The information includes weight, length, depth and width of every individual fish.